2011
DOI: 10.1590/s1517-83822011000100033
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter insulaenigrae: first isolation report from South American sea lion (Otaria flavescens, (Shaw, 1800)

Abstract: Campylobacter insulaenigrae have been isolated from different pinnipeds but not from South American sea lion (Otaria flavescens).The aim of this work is to report the first isolation of C. insulaenigrae from South American sea lion (Otaria flavescens).The isolate, identified by its phenotypic and molecular characteristics, allow recognizing O. flavescens as a new host for C. insulaenigrae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…; González et al . ), in this study, is worthy of note. However, the high prevalence of Campylobacter in the grey seals ( Halichoerus grypus ) inhabiting the breeding colony of the Isle of May in the Firth of Forth (Scotland, UK) may reflect the intense human activity in this area and possible infection from human or livestock sources.…”
Section: Discussionsupporting
confidence: 52%
“…; González et al . ), in this study, is worthy of note. However, the high prevalence of Campylobacter in the grey seals ( Halichoerus grypus ) inhabiting the breeding colony of the Isle of May in the Firth of Forth (Scotland, UK) may reflect the intense human activity in this area and possible infection from human or livestock sources.…”
Section: Discussionsupporting
confidence: 52%
“…Other members of the C. lari group are also isolated from gulls (UPTC, C. volucris [ Kaneko et al 1999 ; Debruyne et al 2010b ]) and other shorebirds, such as plovers, redshanks, dunlins, sandpipers, skuas, albatrosses, and penguins ( C. lari , UPTC, C. subantarcticus [ Waldenstrom et al 2002 , 2007 ; Leotta et al 2006 ; Debruyne et al 2010a ; Ryu et al 2014 ]). The C. lari group strains are also isolated from marine mammals ( C. insulaenigrae , C. lari [ Foster et al 2004 ; Stoddard et al 2007 ; Garcia-Pena et al 2010 ; Gonzalez et al 2011 ]), shellfish ( C. lari , C. peloridis [ Endtz et al 1997 ; Van Doorn et al 1998 ; Debruyne et al 2009 ]), and seawater/fresh water ( C. lari , UPTC [ Obiri-Danso and Jones 1999 ; Obiri-Danso et al 2001 ; Meinersmann et al 2013 ; Khan et al 2014 ]). Even though members of the C. lari group have been isolated from livestock ( Tresierra-Ayala et al 1994 ; Aarestrup et al 1997 ; Harvey et al 1999 ; Scanlon et al 2013 ), this clade is primarily associated with coastal regions and watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…There are also records of the species entering river mouths (basin of the Uruguay River, basin of the Santa Lucía River, Arroyo Pando and Arroyo Solís in Uruguay) and Atlantic coastal lagunes. The sporadic presence of SASL individuals in the Valdivia River is a phenomenon observed through decades and scientifically documented since 1976 ( González et al , 2011 ). In the last decade, a colony of about 30 to 40 animals was established in a coastal area of the urban course of the Valdivia River (39°47’Southern latitude, 73°15’ Western latitude), with the river being their feeding ground; whilst they use the sandy beach by the river, the lawn and the pavement of the street in the surrounding areas as resting ground.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted us to look for the presence of zoonotic intestinal bacteria in fresh sea lions feces placed on the pavement. During the course of this investigation, Campylobacter insulaenigrae ( González et al , 2011 ) and several species of the Family Enterobacteriaceae were isolated ( González et al , 2010 ), with Edwardsiella tarda being the most frequently found (73%) ( González et al , 2010 ). This is a zoonotic bacterium that has been isolated from humans, animals, and the environment and it is particularly considered a fish pathogen, being the only species of its genus that has been reported to be pathogenic to humans ( Leung et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%